Influence of teacher competences on reading comprehension achievement among students with learning disabilities in Ibadan North Local Government Area, Oyo state (2017)
This study investigated the relationship between teacher competences (subject mastery, teaching methodology and compliance with teaching obligations) and reading comprehension achievement of students with learning disabilities in Ibadan North Local Government Area of Oyo State, Nigeria. The study adopted a survey design. Thirty (30) Senior Secondary Class 2 students, from six schools identified as having learning disabilities in reading comprehension participated in the study. Four instruments were used in the study. These were the Learning Disability Evaluation Scale Renormed, Second Edition (LDES-R2) for screening students for learning disabilities (r =0.75), the Reading Comprehension Test (RCT) (r = 0.81), Teachers’ Competence and Performance Questionnaire (TCPQ) (r= 0.85) and the Achievement Test in Reading Comprehension (ATRC) (r = 0.70). Data collected were analyzed using the Pearson’s product moment correlation and multiple regression analysis. Two research questions and three hypotheses generated were tested at 0.05 level of significance. The results revealed that there is a significant joint relationship between reading comprehension achievement of students with learning disabilities and teacher competences in terms of teacher mastery of subject matter, teaching methodology used by teachers and compliance with teaching obligations by teachers of students with learning disabilities. When the independent variables were considered as individual variables, subject mastery (β = .353, P <.05), made the most contribution to the dependent variable, followed by teacher compliance with teaching obligations (β = .244, P>.05), and then teaching methodology (β =.236, P>.05). On the basis of these findings, recommendations were made which included that teachers of students with learning disabilities should have: adequate mastery of subject matter and up to date lesson plans. They should use a variety of appropriate teaching methods and always identify with professionals bodies in the field of special needs education as they comply with teaching obligations.